Revitalisasi serta Batasan Toleransi Skewness Arah Kiblat dalam Ibadah Menurut Syafi’iyah - Anwar Singosari, Khoirul Anwar Singosari (UIN ALAUDDIN MAKASSAR, 2024)
This paper discusses this issue of revitalizing the Qibla direction in the community, where scholars differ in opinion, about the limits of facing the Qibla. In Imam Syafi'i's view, it is stated that for people who are far away and cannot see the Kaaba directly, then for him to try hard (al-ijtihad) to find out the true Qibla direction by using the clues of the universe. Imam Shafi'i's opinion shows that people who pray must try to face the 'ain al-kakbah with an ijtihad, although in the view of other scholars from among the Shafi'is it is enough with jihad al-kakbah to be valid in praying. This research is a qualitative study with a field research approach and data collection methods in the form of interviews, documentation and observation obtained by the research results. The theory used is a descriptive analysis method that uses the calculation of Qibla direction according to the skewness tolerance limit based on Syafiiyah's study. The conclusion of this paper describes that, first, the revitalization of Qibla direction is important because every mushallin (person who prays) is obliged to face the Qibla, namely facing the Kaaba building either in 'ain al Kakbah or jihah al Kaaba, just like the Meccans. Secondly, the limitation of skewness in Qibla has a tolerance value of 3-4 minutes according to the literacy that refers to Syafi'iyah.